Relationships between physical fitness characteristics, technical skill attributes, and sports injury in female Australian football players. - Jessica B Farley; Miranda O'Hara; Justin W L Keogh; Carl T Woods; Evelyne Rathbone; Nikki Milne (PLoS ONE, 2024)
Objectives To explore the relationships between physical fitness and i) technical skills and ii) time-loss from Australian football injury in female players across the talent and participation pathways. Methods This study uses a subset of data from two cross-sectional and one prospective cohort studies. A total of 223 female Australian football players across five competition levels (elite/non-elite senior, high-level junior, and non-elite junior (14-17 years)/(10-13 years)) were included in this study. Comprehensive physical fitness assessments and modified Australian football kicking and handballing tests were conducted in the 2018/19 pre-seasons. During the respective competitive in-season, time-loss injuries were recorded by team personnel. Stepwise multiple linear regressions were performed to determine the relationship between physical fitness and kicking and handballing scores. Cox proportional regressions were conducted to identify physical fitness factors associated with injury. Results Increased running vertical jump height, greater hip abduction strength, and faster timed 6 m hop speed demonstrated a relationship with kicking accuracy when adjusted for years of Australian football playing experience (adjusted R2 = 0.522, p < 0.001). Faster agility time and increased lean mass were associated with better handballing accuracy (adjusted R2 = 0.221, p < 0.001). Multivariate Cox regression revealed an increased risk for sustaining a time-loss injury in less agile players (adjusted HR 2.41, 95% CI 1.23, 4.73, p = 0.010). However, this relationship no longer remained when adjusted for age and years of Australian football experience (adjusted HR 1.68, 95% CI 0.81, 3.50, p = 0.166). Conclusions Physical fitness may be a significant factor contributing to development of Australian football technical skills in female players. However, its role is unclear in protecting against injury risk in this athlete population. Further research is needed to explore the multifactorial and complex phenomenon of talent development and injury risk reduction in female Australian football players.